Local Food-Based Local Content Learning: Utilizing Avocado Seed Flour as a Substitute for Wheat Flour in Making Cookies for Elementary School Students - Guri, Guri; Salsabilah, Wanada Siti; Perdana, Rahmat; Rizqiyah, Nabila Nur; Oktavia, Sri Wina (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to integrate local food resources into Local Content (Muatan Lokal) learning for elementary school students by utilizing avocado seed flour as a substitute for wheat flour in cookie production. Methodology: The research was conducted using a Completely Randomized Design (CRD) with six treatment levels of avocado seed flour substitution and five replications. The procedures included the preparation of avocado seed flour following food science standards, cookie production using a standardized baking method, and evaluation of physical properties consisting of moisture content, water activity, hardness, and color. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Main Findings: The findings show that increasing the proportion of avocado seed flour significantly affected the physical properties of cookies, particularly reducing moisture content and increasing hardness, while also influencing color parameters (L, a, b*). Novelty/Originality of this study: The novelty of this study lies in the integration of multidisciplinary food science methods with elementary education through the development of a local food–based learning model that promotes contextual, hands-on learning using local resources. This approach strengthens food literacy and supports character development related to sustainability and the appreciation of local biodiversity.